A novel TBK1/IKKϵ is involved in immune response and interacts with MyD88 and MAVS in the scallop Chlamys farreri - Liu, Wenjuan; Ma, Jilv; Chen, Jiwen; Huang, Baoyu; Liu, Fengchen; Li, Lingling; Fan, Nini; Li, Fangshu; Zheng, Yanxin; Zhang, Xuekai; Wang, Xiaona; Wang, Xiaomei; et al. (Frontiers in Immunology, 2023)
Inhibitor of κB kinase (IKK) family proteins are key signaling molecules in the animal innate immune system and are considered master regulators of inflammation and innate immunity that act by controlling the activation of transcription factors such as NF-κB. However, few functional studies on IKK in invertebrates have been conducted, especially in marine mollusks. In this study, we cloned the IKK gene in the Zhikong scallop Chlamys farreri and named it CfIKK3. CfIKK3 encodes a 773-amino acid-long protein, and phylogenetic analysis showed that CfIKK3 belongs to the invertebrate TBK1/IKKϵ protein family. Quantitative real-time PCR analysis showed that CfIKK3 mRNA is ubiquitously expressed in all tested scallop tissues. The expression of CfIKK3 transcripts was significantly induced after challenge with lipopolysaccharide, peptidoglycan, or poly(I:C). Co-immunoprecipitation (co-IP) assays confirmed the direct interaction of CfIKK3 with MyD88 (the key adaptor in the TLR pathway) and MAVS (the key adaptor in the RLR pathway), suggesting that this IKK protein plays a crucial role in scallop innate immune signal transduction. In addition, the CfIKK3 protein formed homodimers and bound to CfIKK2, which may be a key step in the activation of its own and downstream transcription factors. Finally, in HEK293T cells, dual-luciferase reporter gene experiments showed that overexpression of CfIKK3 protein activated the NF-κB reporter gene in a dose-dependent manner. In conclusion, our experimental results confirmed that CfIKK3 could respond to PAMPs challenge and participate in scallop TLR and RLR pathway signaling, ultimately activating NF-κB. Therefore, as a key signaling molecule and modulator of immune activity, CfIKK3 plays an important role in the innate immune system of scallops.